Acoustic features of voice in adults suffering from depressio - Calić, Gordana; Petrović-Lazić, Mirjana; Mentus, Tatjana; Babac, Snežana (Psihološka istraživanja, 2022)
This research aimed to examine whether the acoustic features of voice were different and discriminant in people suffering from depression (experimental group – EG) compared to the typically developing population (control group 1 – CG1) and people with the diagnosed psychogenic voice disorder (control group 2 – CG2). The sample included 51 participants (18 in EG, 24 in CG1, and 9 in CG2). Nine acoustic parameters were analyzed on the basis of the sustained phonation of the vowel /a/. The MDVP software program (“Kay Elemetrics” Corp., model 4300) was used in the acoustic analysis. The results showed that the mean values of all acoustic parameters differed in people suffering from depression compared to both control groups as follows: Jitter, Shimmer, NHR, vAm, APQ, and VTI parameters were higher, SPI was lower compared to both control groups, and F0 was lower compared to CG1. Only the PPQ parameter was not significant. Shimmer, vAm, APQ, and VTI parameters had the highest discriminant value for depression. The acoustic features of voice, analyzed in this study with regard to the sustained phonation of a vowel, were different and discriminant in the EG compared to CG1 and CG2. In voice analysis, the parameters Shimmer, vAm, APQ, and VTI could potentially be the markers indicative of depression.